An advanced workflow for single-particle imaging with the limited data at an X-ray free-electron laser. (2020) - Assalauova, Dameli; Kim, Young Yong; Bobkov, Sergey; Khubbutdinov, Ruslan; Rose, Max; Alvarez, Roberto
No abstract available